Structural Change or Path Dependence? Assessing the Growth Paths of Sub-Saharan African Economies - (:unkn) unknown (My University, 2014)
Sub-Saharan African economies have exhibited spectacular growth rates since the early-2000s. For many observers, this marks the end of the pessimism that has long prevailed in the economic literature on the region. The paper argues that uncertainties remain, however. Growth rates mostly stem from distorted export structures - based on commodities -, and high international commodity prices due to demand from China and other emerging countries. These growth rates may not imply any change of export structures (which may even be strengthened), they remain vulnerable to price fluctuations and external shocks, and they may not involve structural transformation, i.e. a break in the pre-existing structure of the economy, industrialisation and productivity growth. On the other hand, sustained high commodity prices may foster structural transformation via higher fiscal resources; emerging countries also invest in Sub-Saharan African industrial sectors and infrastructure, which are key determinants of structural change; equally, commodities may trigger linkages towards industrialisation. The relative strengths of these arguments are assessed.
Keywords: African Research